Pesantrenpreneur dan Sosiopreneur sebagai Alternatif Gerakan Moderasi Ekonomi Pasca Pandemi di Pesantren Yogyakarta - Kurniawan, Muhammad Arif (Department of Islamic Economics, Faculty of Islamic Religion, Yudharta University Pasuruan, East Java, Indonesia., 2022)
This research aimed to find out about pesantrenpreneur and sociopreneur at Islamic boarding schools (pesantren) as alternatives to post-Covid-19 economic moderation in two pesantren in Yogyakarta, namely Integrated Islamic Boarding School of Al Mumtaz, Gunungkidul Regency and Islamic Boarding School of ISC Aswaja Lintang Songo, Bantul Regency. This research was a qualitative research with a case study approach. Collecting data used observation, structured interviews, and documentation. While the data analysis technique used the Miles and Huberman model analysis. The research results showed that the two Islamic boarding schools in Yogyakarta had carried out various activities based on the concept of pesantrenpreneur and sociopreneur with four important stages, namely 1) the pesantren apprenticeship stage, 2) the pesantren launching stage, 3) the pesantren take-off stage, and 4) the pesantren maturity stage. The four stages were carried out well, especially to recover post-Covid-19 economic growth of pesantren and the surrounding community more optimally.